State social assistance to low-incover families in the conditions of marital state - Trufanova, Yuliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
In the article, the author highlights the issues of legal regulation of the institute of state social assistance to low-income families. Social protection of families with children receives special attention in modern socio-economic conditions during martial law.The Constitution of Ukraine declares that a person, his life and health, honor and dignity, inviolability and security are recognized as the highest social value in Ukraine. A special place in the social protection system belongs to social protection of families with children.The author outlined the range of legislative acts regulating this issue, as well as highlighted the latest changes introduced by Resolution of the Cabinet of Ministers of Ukraine No. 214 dated 07.07.2022 "On some issues of providing state social assistance" and Resolution of the Cabinet of Ministers of Ukraine No. 332 dated 03.22.2022 "Some issues payment of accommodation allowance to internally displaced persons", etc.In the course of life of a family dependent on minor children, a large number of social risks are expected, including poverty, disability, illness, which requires the state to develop and adopt new social programs aimed at protecting these segments of the population, social security from adverse consequences and risks.Thus, the state social support of families with children, in the conditions of martial law, is an important direction of the state policy regarding children in Ukraine and is an actual topic today.The purpose of the article is to analyze the legislation on the provision of state social assistance to families on the verge of poverty in connection with the large-scale military invasion of Ukraine and the introduction of martial law in Ukraine.The problem of state social support for low-income families with children requires special attention today.